2015
DOI: 10.3856/vol43-issue1-fulltext-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of endemic microalgae as potential food for Artemia franciscana culture

Abstract: ABSTRACT. In this study, five microalgal strains were isolated from Bahía de La Paz, Baja California Sur, Mexico and identified as Grammatophora sp., Navicula sp., Rhabdonema sp., Schizochytrium sp., and Nitzschia sp., and their evaluation as potential food for Artemia franciscana. The isolated strains were cultured outdoors and harvested after four days. Chaetoceros muelleri was cultured under laboratory conditions and used as control. The protein, lipid, and carbohydrate composition and the fatty acid profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
9
0
2
Order By: Relevance
“…A decrease in cyst production is now observed due to global reduction in the habitats traditionally used to harvest Artemia cysts, due to climate changes and human intervention, and it is expected that this crisis will deepen (AghaKouchak et al, ; Asem, Mohebbi, & Ahmadi, ; Shadrin, Anufriieva, & Galagovets, ; Wurtsbaugh et al, ). Intensive cultivation and creation of new Artemia populations (by intentional introduction) in salt lakes (previously without Artemia ) are developing now (Anh, Van Hoa, Van Stappen, & Sorgeloos, ; Jia et al, ; Pacheco‐Vega, Cadena Roa, Ascencio, Rangel Davalos, & Rojas Contreras, ; Sultana et al, ; Tackaert & Sorgeloos, ), but this cannot contribute significantly to satisfy the required world demand on cysts. Another option to sharply increase the world's Artemia cyst harvest is the new natural habitats of Artemia spp.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in cyst production is now observed due to global reduction in the habitats traditionally used to harvest Artemia cysts, due to climate changes and human intervention, and it is expected that this crisis will deepen (AghaKouchak et al, ; Asem, Mohebbi, & Ahmadi, ; Shadrin, Anufriieva, & Galagovets, ; Wurtsbaugh et al, ). Intensive cultivation and creation of new Artemia populations (by intentional introduction) in salt lakes (previously without Artemia ) are developing now (Anh, Van Hoa, Van Stappen, & Sorgeloos, ; Jia et al, ; Pacheco‐Vega, Cadena Roa, Ascencio, Rangel Davalos, & Rojas Contreras, ; Sultana et al, ; Tackaert & Sorgeloos, ), but this cannot contribute significantly to satisfy the required world demand on cysts. Another option to sharply increase the world's Artemia cyst harvest is the new natural habitats of Artemia spp.…”
Section: Introductionmentioning
confidence: 99%
“…In Artemia production manuals, many efforts have made to help to choose suitable species/populations to be applied in aquaculture industry (Tackaert & Sorgeloos, 1991;Lavens & Sorgeloos, 1991Barata, Hontoria, & Amat, 1996;Thi, Van, & Sorgeloos, 2013). Additionally, the effect of environmental parameters was studied on potential of cyst production (Barata et al, 1996;Thi et al, 2013;Gao, Wang, Ma, Stappen, & Sui, 2017Nguyen, 2015;Thi, Pachecovega, Cadenaroa, Ascencio, Rangeldávalos, & Rojascontreras, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…is a benthic diatom that presents approximate dry weight levels of 430-490 g/kg of protein, 230-260 g/kg of lipids, which are 30-150 g of EPA g/kg and 20-30 g of DHA g/kg (Khatoon, Banerjee, Yusoff, & Shariff, 2009). Other studies have shown that the lipid content ranges from 4.3% to 31.7% and protein from 12.7% to 13.31% (Courtois, Viera, Huchetteb, & Izquierdo, 2012;Pacheco-Vega, Cadena-Roa, Ascencio, Rangel-Dávalos, & Rojas-contreras, 2015). In this context, some studies using Navicula sp.…”
mentioning
confidence: 99%